Cultivated land protection policies in China facing 2030: Dynamic balance system versus basic farmland zoning. (November 2017) - Wu, Yuzhe; Shan, Liping; Guo, Zhen; Peng, Yi
Abstract: The Chinese central government launched two principal campaigns to maintain the quantity and quality of cultivated land across the country and to continuously sustain a growing population. Dynamic balance system and basic farmland zoning focus on protecting the quantity and quality of cultivated lands, respectively. Theoretically, two complementary campaigns can effectively protect the quantity and quality of cultivated land. However, these policies protect the quality of cultivated land minimally. Dynamic balance system replaces basic farmland protection system during implementation by transforming from control planning to development planning. The process increases the conversion of high quality cultivated land into industrial and residential uses, with the supplementary of cultivated land with low quality, thereby reducing the protection on the quality of this land. This study adopts Yiwu City as the study case and analyzes the administration efficiency of dynamic balance system and basic farmland zoning. Evidence suggests that the delimitation of permanent basic farmland is a feasible system arrangement. The central government should deal with the relationships among policies to protect the quantity, quality, and ecosystem of the cultivated land. The government can arrange permanent basic farmland zoning as the core system for cultivated land protection and practice grade protection system on basic farmlands to strictly limit their conversion into construction land, which inevitably weakens the dynamic balance system. Highlights: We study the China's cultivated land protection policies especially facing 2030. Two kinds of cultivated land protection policies are compared. A framework has been given in order to have a better comparison of the two kinds of policies. Yiwu city is analyzed as a case, and solutions for the cultivated land protection are suggested.